Guattari: machines and political subjects - Agostinho, Larissa Drigo (Faculdade de Filosofia e Ciências, 2021)
From a presentation of the political and social context within which Guattari’s work fits in, we seek to define the French political debate of the 1960s in the field of Marxism – especially historical materialism – on the question of the subject of history. The purpose of this article is to explain the reasons that lead Guattari to break with structuralism, represented in psychoanalysis by Lacan and Marxism by Althusser. The relevance of this article lies in the presentation of the concept of machine, which is defined in opposition to the concept of structure and that, joining history and unconscious, aims to trace the emergence space of a subject of history, of a political subject. Recebido: 18/09/2017Aceito: 30/06/2019